Alcohol consumption among women rugby players in France: Uses of the "third half-time". (June 2014) - Fuchs, Julien; Le Hénaff, Yannick
This article explores alcohol consumption among women rugby players, particularly during the "third half-time", which traditionally takes place after the matches. The article will focus on alcohol use and the transgression of the norms of femininity. A series of ethnographic observations were carried out and semi-structured interviews were conducted with players ( n = 10) from an amateur league-level women's rugby team in Western France. The results show that within the context of rugby – which is marked by festive excesses and has been socially constructed as a "male" sport – women have a specific relationship with alcohol; although drinking is deemed necessary to demonstrate their inclusion in so-called "rugby culture", it is, nevertheless, far from being completely unrestrained. On the contrary, some of its effects are a construct of the group itself. In this sense, drinking in the third half-time poses a dilemma for women: how to establish themselves as women rugby players whilst remaining women at the same time.